Penguatan Partisipasi Kaum Muda Katolik Dalam Kehidupan Menggereja - Vitalis Tarsan Vitalis; Florianus Dus Arifian (Unika Santu Paulus Ruteng, 2023)
Currently, the participation of young Catholics in the life of the church is very concerning. Their motivation, interest and concern for the growth and development of the Church, here and now, is very low. This problem is also experienced by most young Catholics in the Holy Spirit Stasi, Arus, Bangka Arus Village, East Lamba Leda District, East Manggarai Regency. So that, the solution offered by the PkM team to this problem is an effort to assist and re-strengthen their participation in church life. The stages and methods in this empowerment activity are starting with preparation and planning, then organizing and assisting activities, and ending with monitoring and evaluation. The target of this PkM is all young Catholics in Arus, Bangka Arus Village, District Lamba Leda Timur, East Manggarai Regency. The final results of the PkM show that the Catholic youth in the Holy Spirit, Arus, was very enthusiastic in participating in ecclesiastical activities. They are increasingly aware of and paying attention to the life of the church, especially in aspect fellowship, worship, preaching, and aspects of service.